Neurocognitive deficits and effects of cognitive reserve in mild cognitive impairment - Andrejeva, Nadeshda; Knebel, Maren; Santos, Vasco dos; Schmidt, Janna; Herold, Christina; Tudoran, Ruxandra; Wetzel, Petra; Wendelstein, Britta; Meyer-Kühling, Inga; Navratil, Sabrina; Gorenc-Mahmutaj, Lina Sidonija; Rosenbaum, Gerd; et al. (Dementia and geriatric cognitive disorders, 2016)
Background/Aims: Mild cognitive impairment (MCI) is a frequent syndrome in the older population, which involves an increased risk to develop Alzheimer's disease (AD). The latter can be modified by the cognitive reserve, which can be operationalized by the length of school education. MCI can be differentiated into four subtypes according to the cognitive domains involved: amnestic MCI, multiple-domain amnestic MCI, non-amnestic MCI and multiple-domain non-amnestic MCI. While neurocognitive deficits are a constituent of the diagnosis of these subtypes, the question of how they refer to the cognitive reserve still needs to be clarified. Methods: We examined neuropsychological deficits in healthy controls, patients with MCI and patients with mild AD (n = 485) derived from a memory clinic. To reduce the number of neuropsychological variables, a factor analysis with varimax rotation was calculated. In a second step, diagnostic groups including MCI subtypes were compared with respect to their clinical and neuropsychological characteristics including cognitive reserve. Results: Most MCI patients showed the amnestic multiple-domain subtype followed by the pure amnestic subtype, while the non-amnestic subtypes were rare. The amnestic subtype displayed a significantly higher level of cognitive reserve and higher MMSE scores than the amnestic multiple-domain subtype, which was in most cases characterized by additional psychomotor and executive deficits. Conclusions: These findings confirm earlier reports revealing that the amnestic multiple-domain subtype is the most frequent one and indicating that a high cognitive reserve may primarily prevent psychomotor and executive deficits in MCI.